2009
DOI: 10.4103/0970-9290.59456
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a potential risk factor for chronic obstructive pulmonary disease: A retrospective study

Abstract: On the basis of the observed results of the study it can be concluded that the risk for COPD appeared to be significantly elevated when attachment loss was found to be severe. It is conceivable that oral interventions that improve oral health status may prove to lower the severity of lung infection in susceptible populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 2 publications
7
50
0
5
Order By: Relevance
“…Merely on the basis of a few spirometry parameters, some cross-sectional and case-control studies reported significant associations of periodontal disease with history of COPD and lung function decline [4][5][6][7][8]12]. Furthermore, periodontal disease has been related to the longitudinal decline in spirometric lung volumes [9,10,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merely on the basis of a few spirometry parameters, some cross-sectional and case-control studies reported significant associations of periodontal disease with history of COPD and lung function decline [4][5][6][7][8]12]. Furthermore, periodontal disease has been related to the longitudinal decline in spirometric lung volumes [9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have investigated the relationship between periodontitis [4][5][6][7][8][9][10][11][12][13][14] or oral hygiene [12,13,15] and respiratory diseases, although common causes might exist. Both diseases have been related to systemic inflammation [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Kowalski et al examined the periodontal status of 100 patients with COPD, and observed a high prevalence (84.2%) of periodontitis and a positive correlation of PD and PI with the severity of COPD (15). In addition, a high prevalence of CP and obvious resorption of alveolar bone were found in patients with severe COPD (15)(16)(17). Zeng performed a meta-analysis to ascertain the relationship between PD and COPD, and found that PD was a significant and independent risk factor of COPD (18).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that a loss of 20% of the alveolar bone leads to an increased risk for development of COPD by 60%. However, it should be noted that the reduction of FEV1 is related not only to the existence of COPD but also to other respiratory diseases [19].…”
Section: Epidemiology Of Copd and Periodontitismentioning
confidence: 99%